2020
DOI: 10.17305/bjbms.2020.4636
|View full text |Cite
|
Sign up to set email alerts
|

High MTHFR promoter methylation levels in men confer protection against ischemic stroke

Abstract: The MTHFR gene encodes methylenetetrahydrofolate reductase required for the metabolism of homocysteine (Hcy) – a previously reported independent risk factor for ischemic stroke (IS). In this study, we first aimed to clarify the association between DNA methylation levels in the MTHFR promoter and the risk of IS, followed by the analysis of potential interactions between environmental factors and DNA methylation levels that affect IS risk. We recruited 164 patients with hypertension and IS (case group) and 345 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…On the other hand, recent findings associated a reduction of MTHFR methylation with unfavorable conditions or diseases. For example, hypermethylation of the MTHFR promoter has been described as a protective factor against ischemic stroke [ 72 ]. Moreover, it has been demonstrated that MTHFR demethylation is more frequent in subjects that are physically inactive [ 73 ], and that homocysteine can induce demethylation in the promoter region of the MTHFR gene in human vascular smooth muscle cells [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent findings associated a reduction of MTHFR methylation with unfavorable conditions or diseases. For example, hypermethylation of the MTHFR promoter has been described as a protective factor against ischemic stroke [ 72 ]. Moreover, it has been demonstrated that MTHFR demethylation is more frequent in subjects that are physically inactive [ 73 ], and that homocysteine can induce demethylation in the promoter region of the MTHFR gene in human vascular smooth muscle cells [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Additionally, blood methylation in dozens of genes have been associated with stroke risk and functional outcomes in stroke patients with comorbid diseases (hypertensive and obese). [49][50][51] Furthermore, additional profiling studies showed that biological age (DNAm age), which is measured by circulating levels 5mC, can predict stroke risk, outcome, and recurrence more accurately than chronological age. [52][53][54][55][56] Thus, these studies collectively indicate that blood levels of methylated DNA may serve as a biomarker for the diagnosis, prognosis and treatment of stroke.…”
Section: Stroke and Dna Methylationmentioning
confidence: 99%
“…Elevated homocysteine levels can induce an excessive inflammatory response in the cerebral region [ 68 ]. Furthermore, high MTHFR promoter methylation levels are suggested to lower the risk of ischemic stroke [ 7 , 75 ]. These findings support the possibility of using the methylation status of MTHFR promoter as a predictive biomarker for ischemic stroke; however, additional studies are required to confirm this hypothesis.…”
Section: Dna Methylation In Neuroprotection After Strokementioning
confidence: 99%